Agricultural development networks in 14 research sites: Findings from the CCAFS Organizational Baseline Survey - Rudnick, Jessica; Niles, Meredith; Lubell, Mark; Cramer, Laura K. (2019)
This brief summarizes findings from a network analysis using data from the CCAFS Organizational Baseline Surveys (OBS) to analyze how organizations in CCAFS sites coordinate to work together on climate change and agriculture initiatives.